Pendidikan kesehatan cuci tangan dan pemeriksaan tumbuh kembang anak dengan media KPSP dan Denver II - Setiawati, Setiawati; Sari, Ayi Puspita; Yusuf, Dodi Iqbal; Puta, Dava Arya; Kusumaningrum, Dyah Intan; Sari, Walenda Pitri Novidia; Kumala, Ajeng Dyah; Ferisca, Fidela; Wahyuningsih, Indah; Hasanah, Uswatun (JOURNAL of Public Health Concerns, 2026)
Background: Handwashing with soap is an essential part of Clean and Healthy Living Behaviors, which plays a role in preventing infectious diseases in children. However, at the Pasir Gintung Health Post within the Simpur Community Health Center in Bandar Lampung, proper handwashing practices are still low, as are parents and cadres' limited knowledge regarding growth and development screening using the DPSQ and Denver II. Purpose: To increase knowledge regarding standard handwashing and improve cadres' ability to perform growth and development screening using the DPSQ and Denver II. Method: This community service activity was carried out on November 29, 2025 at the Pasir Gintung Health Post, the working area of ​​the Simpur Bandar Lampung Health Center. This activity was attended by 10 parents and their children and 3 health cadres. The activity used a media-based health education approach and practical supervision to improve the knowledge and skills of parents and health cadres regarding handwashing with soap behavior and child growth and development examinations using DPSQ and Denver II. The child growth and development examination instruments used DPSQ sheets, Denver II forms, and standard guidebooks. Evaluation of the activity was carried out using questionnaires to participants before the educational activity (pre-test) and after the educational activity (post-test) regarding the importance of handwashing with soap, important times for handwashing, and handwashing steps according to WHO standards, while evaluation for health cadres included supervision and observation of cadres in conducting child growth and development screening using DPSQ and Denver II regarding the importance of early detection and follow-up steps if there is suspicion of growth and development delays in children. Results: Data obtained on the level of knowledge of participants regarding handwashing stages before the educational activity showed that 3 participants (30.0%) were in the good category and 7 participants (70.0%) were in the poor category. After the educational activity, 9 participants (90.0%) were in the good category and 1 participant (10.0%) were in the poor category. Meanwhile, regarding the practical actions of participants in washing their hands correctly before the educational activity, 5 participants (50.0%) were in the good category and 5 participants (50.0%) were in the poor category. After the educational activity, 9 participants (90.0%) were in the good category and 1 participant (10.0%) was in the poor category. Conclusion: Health education activities using proposals, SAP, and leaflets, as well as direct demonstrations, were effective in increasing knowledge and skills in implementing proper handwashing with soap according to standards. Increased community knowledge and cadre skills contribute to changes in community behavior towards healthy living and early detection as an effort to prevent the causes of child development problems. Suggestion: It is hoped that the handwashing health education program, along with supervision of DPSQ examinations and child development, can be implemented sustainably and integrated with maternal and child health service programs. Health workers are expected to continue improving their competencies through regular training on effective health education techniques and the appropriate and consistent use of DPSQ instruments. Keywords: Child development; Denver II; DPSQ; Handwashing; Health cadres; Health education Pendahuluan: Cuci tangan pakai sabun merupakan bagian penting dari Perilaku Hidup Bersih dan Sehat (PHBS) yang berperan dalam mencegah penyakit infeksi pada anak. Namun, di Poskeskel Pasir Gintung wilayah kerja Puskesmas Simpur Bandar Lampung, masih ditemukan rendahnya praktik cuci tangan yang benar serta keterbatasan pengetahuan orang tua dan kader mengenai pemeriksaan tumbuh kembang menggunakan KPSP dan Denver II. Tujuan: Untuk meningkatkan pengetahuan mengenai cuci tangan sesuai standar dan peningkatan kemampuan kader dalam melakukan deteksi tumbuh kembang melalui pemeriksaan KPSP dan Denver II. Metode: Kegiatan pengabdian masyarakat ini dilaksanakan pada tanggal 29 November 2025 di Poskeskel Pasir Gintung, wilayah kerja Puskesmas Simpur Bandar Lampung. Kegiatan ini diikuti 10 orang tua beserta anaknya dan 3 orang kader kesehatan. Kegiatan menggunakan pendekatan edukasi kesehatan berbasis media dan supervisi praktik untuk meningkatkan pengetahuan serta keterampilan orang tua dan kader kesehatan terkait perilaku cuci tangan pakai sabun serta pemeriksaan tumbuh kembang anak menggunakan KPSP dan Denver II. Instrumen pemeriksaan tumbuh kembang anak menggunakan lembar KPSP, form Denver II, dan buku panduan standar. Evaluasi kegiatan dilakukan dengan menggunakan kuesioner kepada peserta sebelum kegiatan edukasi (pre-test) dan sesudah kegiatan edukasi (post-test) mengenai pentingnya cuci tangan pakai sabun, waktu-waktu penting untuk cuci tangan, serta langkah-langkah mencuci tangan sesuai standar WHO, sedangkan evaluasi untuk kader kesehatan berupa supervisi dan observasi pada kader dalam melakukan skrining pemeriksaan tumbuh kembang anak dengan menggunakan KPSP dan Denver II mengenai pentingnya deteksi dini dan langkah tindak lanjut jika ditemukan kecurigaan keterlambatan tumbuh kembang pada anak. Hasil: Mendapatkan data tingkat pengetahuan peserta tentang tahapan cuci tangan sebelum kegiatan edukasi sebanyak 3 orang (30.0%) dalam kategori baik dan dalam kategori kurang sebanyak 7 orang (70.0%), sedangkan sesudah kegiatan edukasi menjadi dalam kategori baik sebanyak 9 orang (90.0%) dan dalam kategori kurang sebanyak 1 orang (10.0%). Sementara itu, untuk tindakan praktik peserta dalam melakukan cuci tangan dengan benar sebelum kegiatan edukasi yang dalam kategori baik sebanyak 5 orang (50.0%) dan dalam kategori kurang sebanyak 5 orang (50.0%), sedangkan sesudah kegiatan edukasi menjadi dalam kategori baik sebanyak 9 orang (90.0%) dan dalam kategori kurang 1 orang (10.0%). Simpulan: Kegiatan edukasi kesehatan dengan menggunakan media proposal, SAP, dan leaflet, serta praktik langsung demonstrasi, efektif mampu meningkatkan pengetahuan dan keterampilan dalam melaksanakan perilaku cuci tangan pakai sabun yang benar sesuai standar. Meningkatnya pengetahuan masyarakat dan keterampilan kader memberikan kontribusi terhadap perubahan perilaku masyarakat untuk hidup sehat dan deteksi dini sebagai upaya pencegahan penyebab masalah tumbuh kembang anak. Saran: Diharapkan, program pendidikan kesehatan cuci tangan serta supervisi pemeriksaan KPSP dan perkembangan anak dapat dilaksanakan secara berkelanjutan dan terintegrasi dengan program pelayanan kesehatan ibu dan anak. Tenaga kesehatan diharapkan terus meningkatkan kompetensi melalui pelatihan rutin terkait teknik edukasi kesehatan yang efektif serta penggunaan instrumen KPSP secara tepat dan konsisten.